Análise das condições de desenvolvimento da ginástica artística no Estado de São Paulo - Lima, Letícia Bartholomeu De Queiroz; Murbach, Marina Aggio; Ferreira, Maria Dilailça Trigueiro De Oliveira; Schiavon, Laurita Marconi (Escola de Educação Física e Esporte da Universidade de São Paulo, 2016)
Abstract This descriptive quantitative paper presents a diagnosis of Artistic Gymnastics (AG) in the state of São Paulo from development conditions of the institutions that promote this sport (existent time of the sport in the institution, equipment’s infrastructure, number of professionals, quantity and level of the gymnasts in male and female). For data collection was used a structured questionnaire with closed questions and the data analysis was made from descriptive statistics. Participated in this study 56 AG coaches responsible for 28 institutions from 18 cities of the State of São Paulo. The collected data show that conditions designed for practice are not satisfactory regarding to the development conditions for AG in competitive level, with few professionals related to the number of practitioners, few practitioners in sport initiation, which directly influences the low amount of gymnasts in competitive level and many institutions do not have at least the official equipment of the sport. The non-appropriated conditions of AG development in the state of São Paulo complicate and directly influence the potential to revelation and development of gymnasts to high performance sport in the state. These results may directly reflect on Brazilian AG since São Paulo is a representative State in Brazilian championships and the São Paulo Gymnastics Federation has the largest number of affiliated entities in the country.

Resumo Este artigo, quantitativo descritivo, apresenta um diagnóstico da Ginástica Artística (GA) no interior do Estado de São Paulo a partir das condições de desenvolvimento das instituições que a promovem (tempo de existência da modalidade na instituição, infraestrutura de aparelhagem, número de profissionais, quantidade e nível dos ginastas no feminino e no masculino). Foi utilizado um questionário estruturado com perguntas fechadas para a coleta de dados, os quais foram analisados a partir da estatística descritiva. Fizeram parte deste estudo 56 técnicos/professores de GA, responsáveis por 28 instituições de 18 cidades do interior do Estado de São Paulo. Os dados coletados mostram que as condições destinadas para a prática não são satisfatórias para o desenvolvimento da GA no nível competitivo, há poucos profissionais em relação ao número de praticantes e poucos praticantes na iniciação esportiva, o que influencia diretamente na baixa quantidade de ginastas no nível competitivo. Muitas instituições não possuem ao menos os aparelhos oficiais da modalidade. Isso compromete o desenvolvimento da GA no interior do Estado de São Paulo, dificultando e influenciando diretamente o potencial de revelação e desenvolvimento de ginastas para o alto rendimento esportivo no Estado. Esses resultados podem refletir diretamente na GA brasileira, uma vez que São Paulo é um Estado bastante representativo em Campeonatos Brasileiros, e a Federação Paulista de Ginástica possui o maior número de entidades filiadas no País.
Analysis of the conditions for the development of artistic gymnastics in the State of São Paulo
Keywords: Gymnastics; Infrastructure; Coach; Sports; Ginástica; Infraestrutura; Técnico; Esportes